Taxing Banks Fairly - Mullineux, Andy (Elsevier BV * North-Holland, 2012)
There is no reason to continue to exempt financial services and products from Value Added Tax in the UK, and indeed elsewhere. Its introduction in the UK would help to precipitate the end of the iniquitous and inefficient ‘free banking’ system. Its demise should be enforced by a retail banking and insurance utility regulator that would assure that charges to customers reflect costs incurred by banks and thus eliminate the cross-subsidisation underpinning ‘free banking’. Further, the shareholders and senior bondholders of ‘too big to fail’ banks enjoy a guarantee from taxpayers which they are not paying for. This puts them at a competitive advantage in relation to smaller banks and exposes taxpayers to losses in crises. The big banks should thus pay regulatory and fiscal taxes commensurate with the insurance they enjoy and these taxes should be carefully calibrated so as not to overburden domestic banks relative to international competitors. The taxes paid should relate to a bank's risk exposure and the risks a bank poses to the financial system as a whole. The banks should thus contribute proportionately (with other taxpayers) to producing the Public Good, financial stability. The issue of the tax bias caused deductibility of interest, but not dividend payments, as business expense is also explored. To achieve equal treatment of debt and equity, deductibility could be extended to dividends, but the tendency toward over indebtedness might be curbed if tax deductibility of interest was eliminated, perhaps starting with banks!